14.6k views
2 votes
The steps for solving 7x + 3 = 52 are shown. Explain how each step helps solve the

equation. Include the phrases, "Isolate the variable by -" "Simplify," and "Isolate
the variable term by -" in your answers.
Original equation
7x +3 - 52
7x +3-3-52-3
7x = 49
7x49
TT
x = 7

1 Answer

6 votes

Answer:

The steps for solving 7x + 3 = 52 are shown. Explain how each step helps solve the

Explanation:

Simplifying

7x + 3 = 52

Reorder the terms:

3 + 7x = 52

Solving

3 + 7x = 52

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.

3 + -3 + 7x = 52 + -3

Combine like terms: 3 + -3 = 0

0 + 7x = 52 + -3

7x = 52 + -3

Combine like terms: 52 + -3 = 49

7x = 49

Divide each side by '7'.

x = 7

Simplifying

x = 7

User Juhlila
by
6.4k points